2017
DOI: 10.4102/jsava.v88i0.1397
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced diagnosis of rabies and molecular evidence for the transboundary spread of the disease in Mozambique

Abstract: Rabies is a neglected zoonotic disease with veterinary and public health significance, particularly in Africa and Asia. The current knowledge of the epidemiology of rabies in Mozambique is limited because of inadequate sample submission, constrained diagnostic capabilities and a lack of molecular epidemiological research. We wanted to consider the direct, rapid immunohistochemical test (DRIT) as an alternative to the direct fluorescent antibody (DFA) for rabies diagnosis at the diagnostic laboratory of the Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Therefore, it will be particularly beneficial if rabies diagnosis is decentralized to include the dRIT testing, enabling every state to perform primary diagnosis before sending the samples to the reference laboratories for confirmatory testing should the need arise. These findings demonstrated that the dRIT is capable of detecting low rabies-positive samples, supporting previous reports that the dRIT assay is not only extremely effective, but also reliable and well-suited to resource-limited settings such as Nigeria where sample conditions will not always be optimal [26,27,31,32,33,52]. Coupled with this, the cost of the routine use of the dRIT makes this assay ideal for decentralized rabies diagnosis in resource-limited settings such as Nigeria.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Therefore, it will be particularly beneficial if rabies diagnosis is decentralized to include the dRIT testing, enabling every state to perform primary diagnosis before sending the samples to the reference laboratories for confirmatory testing should the need arise. These findings demonstrated that the dRIT is capable of detecting low rabies-positive samples, supporting previous reports that the dRIT assay is not only extremely effective, but also reliable and well-suited to resource-limited settings such as Nigeria where sample conditions will not always be optimal [26,27,31,32,33,52]. Coupled with this, the cost of the routine use of the dRIT makes this assay ideal for decentralized rabies diagnosis in resource-limited settings such as Nigeria.…”
Section: Discussionsupporting
confidence: 83%
“…Another diagnostic test recently recommended by the OIE for confirmatory rabies diagnosis is either a conventional polymerase chain reaction (PCR) or a quantitative real-time PCR (qRT-PCR) that has passed the OIE Standards for validation [22]. While the detection of amplified viral nucleic acid is a highly effective diagnostic principle, resource-limited countries often lack the necessary infrastructure-namely an appropriate cold chain and dedicated PCR rooms to minimize contamination during amplification of specific viral nucleic acids [32,33]. These limitations prevent the implementation of advanced molecular techniques in Nigeria [9,23].…”
Section: Introductionmentioning
confidence: 99%
“…Presently, with the exception of the anti-RV MABs or PABs (which may be self-produced or obtained from the OIE/WHO rabies reference laboratories), all of the other test reagents for the DRIT are available commercially (e.g., distilled water, PBS, TWEEN, formalin, etc.). After a series of incubations, washes and staining, DRIT results are available in ~1 h. Since its original development, the DRIT has been used in Africa, Asia, Europe, the Middle East and the Americas [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Using either MAB or PAB preparations, preliminary sensitivity and specificity values were deemed comparable to the gold standard FAT, with the majority of studies demonstrating complete test agreement, especially when fresh brain samples were tested [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most common possible reasons for incongruent results, viz. antigen degradation/putrefaction and the misinterpretation of fluorescence when performing the DFA test, were all considered [ 12 , 26 , 27 , 28 , 29 , 30 ]. However, sample degradation should be discussed in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…Before the routine implementation of the DRIT assay in Lesotho, a workshop on the implementation and interpretation of the assay was presented in April 2016 by a South African diagnostician experienced in the use and interpretation of the assay [ 12 ]. Over the course of the five-day workshop held at the CVL in Maseru, four local diagnosticians were introduced to the DRIT assay and its use in a diagnostic setting by applying the assay blindly to a cohort of archival samples ( n = 57) that had been found to be either rabies-positive or -negative with the gold standard DFA test.…”
Section: Methodsmentioning
confidence: 99%